Use of rumen bypass fat for early-lactating dairy cows grazing on coast-cross pasture - Vilela, Duarte; Alvim, Maurilio José; de Matos, Leovegildo Lopes; Matiolli, João Batista (Pesquisa Agropecuaria Brasileira, 2002)
The objective of this experiment was to evaluate the effect of a commercial rumen by pass fat source in concentrate offered to dairy Holstein cows at the first part of lactation, grazing coast-cross-1 (Cynodon dactylon (L.) Pers.) pasture. Fourteen cows at the beginning of lactation were fed on 9, 6, and 3 kg/cow/day of concentrate (23.5% CP and 80% TDN) during the first (up to 90 days), second (91 to 180 days) and third period (181 to 273 days), respectively. The animals were distributed in a random design with two treatments: control and test group. The test group (seven cows) was fed addionally on 700 g/cow/day of commercial source of rumen protected fat, as an extra energy source for the first 90 days of the experimental period. The pasture was managed under rotational grazing with one day of occupation, respecting a resting period of 25 days (spring/summer) to 32 days (fall/winter), for each paddock. Average milk yield, during the three periods, increased (P 0.05) of interaction between type of supplement and period, indicating the prevalence of a residual effect of fat supplementation. The overall stocking rate of the pasture was 4.6 cows/ha, resulting in 72.4 kg of fat corrected milk/ha/day for the control group and 80.4 kg/ha/day for the group fed on the rumen protected fat.
Keywords: rotational grazing; supplements; milk yield; milk production